Bank Advertising as an Instrument for Promotional Activity of Financial Institutions - Seta, Weronika; Wrońska, Karolina; Cegiełko, Szymon (Journal of Finance and Financial Law, 2018)
Demanding customers and wide range of products and services offered by financial institutions make a tough barrier for free entry to the financial market. Offering similar or the same products with new name won’t distinguish one organization from competitors, therefore, advertising fulfils an important function. Basing on analysis of chosen by authors banks and marketing activities, the article shows what does the advertising mean and how it influences on banking operations and prospective customers. The article demonstrates also the dependence between marketing spendings and actual financial situations of organization which was presented on the grounds of individual activities on the interbank market.